An Analysis of Educators and Teaching Staffs Perceptions of the Kampus Mengajar Program at SDN 9 Batu - Isra Mirat; Nadirah; Sam Hermasnyah (MultiTech Publisher, 2023)
This research was conducted to analyze teacher’s perceprions through Kampus Mengajar. This research was conducted at SDN 9 Batu, Pitu Riase where the principal, operator and teachers were the respondents. The data collection methods used in this study were interviews and documentation. The data collection methods used in this research are interview and documentation methods. This research used qualitative research method. The results of the research show that the teachers' perceptions of Kampus Mengajar not only provides classroom teaching experience for students, but also help teachers educate and guide students to give better knowledge especially in remote villages and benefits from Kampus Mengajar is very big because there are changes and student progress in learning. Then there is a high motivation that students have to continue learning, increase their knowledge after Kampus Mengajar activities are finished.